2018
DOI: 10.1111/1462-2920.14276
|View full text |Cite
|
Sign up to set email alerts
|

ACI‐1 beta‐lactamase is widespread across human gut microbiomes in Negativicutes due to transposons harboured by tailed prophages

Abstract: Antibiotic resistance is increasing among pathogens, and the human microbiome contains a reservoir of antibiotic resistance genes. Acidaminococcus intestini is the first Negativicute bacterium (Gram-negative Firmicute) shown to be resistant to beta-lactam antibiotics. Resistance is conferred by the aci1 gene, but its evolutionary history and prevalence remain obscure. We discovered that ACI-1 proteins are phylogenetically distinct from beta-lactamases of Gram-positive Firmicutes and that aci1 occurs in bacteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 85 publications
(102 reference statements)
3
25
0
Order By: Relevance
“…It is, however, also possible that a predicted prophage lacks a virome counterpart, which suggests a prophage remnant that is not any longer active in producing an extracellular phage or a phage simply not present in the examined sample. The virome sequences confirmed the previously described prophages 1 and 2 in A. intestini (Rands et al ., ) and prophage 4 we predicted here (Supporting Information Fig. S2A).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…It is, however, also possible that a predicted prophage lacks a virome counterpart, which suggests a prophage remnant that is not any longer active in producing an extracellular phage or a phage simply not present in the examined sample. The virome sequences confirmed the previously described prophages 1 and 2 in A. intestini (Rands et al ., ) and prophage 4 we predicted here (Supporting Information Fig. S2A).…”
Section: Resultsmentioning
confidence: 97%
“…Although we do identify antibiotic resistance genes within prophage contexts, potentially of public health interest, we note that these are actually rare (only three separate examples). Furthermore, these examples are based on only limited bioinformatic evidence: aci1, which we described previously (Rands et al, 2018), is still a credible ARG whose function was demonstrated experimentally by other researchers (Galán et al, 2000).…”
Section: Plasmid-associated Proteins (Supporting Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, during evolutionary history Firmicute phages had to adapt to a different membrane boundary, assuming vertical phage-bacteria co-evolution. An alternative is that 75 Negativicute phages were acquired horizontally from Proteobacteria, plausible given the shared outer cell structure of their bacterial hosts, and possible environmentally since both bacterial groups share an ecological niche in human microbiomes, particularly in the human gut (Rands et al, 2018). 80 We used the unusual relationship between Negativicutes and classical Gram-Positive Firmicutes to investigate phage-bacteria co-evolution.…”
Section: Introductionmentioning
confidence: 99%